2018
DOI: 10.1109/tac.2018.2794413
|View full text |Cite
|
Sign up to set email alerts
|

Event-Triggered Output Feedback Stabilization via Dynamic High-Gain Scaling

Abstract: This work addresses output feedback stabilization via event triggered output feedback. In the first part of the paper, linear systems are considered, whereas the second part shows that a dynamic event triggered output feedback control law can achieve feedback stabilization of the origin for a class of nonlinear systems by employing dynamic high-gain techniques. arXiv:1605.07425v1 [math.DS]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 30 publications
(63 reference statements)
1
30
0
Order By: Relevance
“…This exponentially convergent term γe − λt can be used to adjust the triggering frequency during the initial stage. Third, the highest powers of the high‐gain parameters in are r or r +1, while here the highest power of the high‐gain parameter in is only 1.…”
Section: Event‐triggered Casade High‐gain Observer With Saturationmentioning
confidence: 87%
See 2 more Smart Citations
“…This exponentially convergent term γe − λt can be used to adjust the triggering frequency during the initial stage. Third, the highest powers of the high‐gain parameters in are r or r +1, while here the highest power of the high‐gain parameter in is only 1.…”
Section: Event‐triggered Casade High‐gain Observer With Saturationmentioning
confidence: 87%
“…By far, a variety of event‐triggered control problems have been studied such as event‐triggered stabilization problem, event‐triggered tracking problem, event‐triggered output regulation problem, event‐triggered state estimation problem, and so on. It is worth mentioning that the event‐triggered high‐gain observer plays an important role in References , , and . Specifically, in Reference , an event‐triggered dynamic high‐gain observer was designed to estimate the state of a class of nonlinear systems satisfying the growth condition, and then an event‐triggered observer‐based output feedback control law was designed to solve the stabilization for the class of nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this fact, the output‐based event‐triggered control is studied by many researchers under different problem setups. The stability of the event‐triggered system with only one triggering mechanism is analyzed, in which both the output transmission and the control application to the plant take place simultaneously . However, due to this, some conservatism are introduced in this event‐triggering approach.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the desired stability of system can be achieved for sufficiently small sampling period (depends on the high‐gain parameter) or with a dual‐mode strategy for the observer for a given sampling period. However, the stability issues of output feedback stabilization in the event‐based design have not been fully explored except for a few works . Recently, the robust‐state estimation using event‐triggered extended state observer is proposed .…”
Section: Introductionmentioning
confidence: 99%